S11 Feasibility of conducting complex physiological measurements in london primary schools: the Size & Lung function in children (SLIC) Study. (14th November 2013) - Lum, S; Sonnappa, S; Wade, A; Kirkby, J; Bonner, R; Lee, S; Bountziouka, V; Legg, S; Raywood, E; Sears, D; Cottam, P; Stocks, J
Abstract : Despite recognised ethnic differences in lung function, most reference ranges are based on White subjects. Ethnic minorities comprise 40% of the London population, which impacts on healthcare provision. Even when available, selection of appropriate equations is complicated by the increase in admixed populations and complexities of defining 'ethnicity'. As part of the Wellcome Trust SLIC study (www.ucl.ac.uk/slic ) to determine the extent to which body shape, size and composition contributes to ethnic differences in lung function, we examined the feasibility of conducting complex physiological measurements in a multi-ethnic population of London primary school children. Methods: 14 London schools participated in the study. Science workshops were presented one week prior to commencing assessments. Consent forms and information packs were distributed to all children. All children with parental consent were eligible and were categorised into 4 broad ethnic groups: White; Black; South-Asian (Indian subcontinent) and Other/mixed. Assessments were performed at school in 5 11 year-old children and included detailed anthropometry, 3D phototonic scan for body shape; body composition; spirometry and saliva samples (cotinine and DNA analysis). Results: Parental consent for anthropometry and spirometry was obtained in 54% of those approached. Amongst these, 88% and 96% provided specific consent for DNA samples and access to GP records respectively (Table 1 ). Assessments were performed in 2175 children (mean (SD)age: 8.22(1.63); 34%White; 29%Black; 25%South-Asian; 12%Other/mixed ethnicities), 1045(48%) of whom had follow-up assessments a year later. Preliminary analysis indicates: 18% had chronic respiratory illness or acute symptoms at time of test. 12% children had a diagnosis of 'asthma ever', with 6% having current asthma (Table 1 ). Acceptable spirometry 1 was obtained from 1574(72%) healthy children. Summary: Conducting a field study to undertake complex physiological measurements is feasible even in young children. However, the relatively high prevalence of chronic or acute respiratory disease at time of testing in this age group, combined with exclusions due to technically unsatisfactory spirometry means that results from ~30% of children may be excluded if analysis of results is to be based on a 'healthy' population. Such factors must be accounted for when designing respiratory field studies to ensure adequate sample size to reach definitive conclusions. Reference: Kirkby et al. Pediatr Pulmonol 2008.